Bridging the Gap - Dorsey, A.D.; Clements, K.; Garrie, R.L.; Houser, S.H.; Berner, E.S (Applied Clinical Informatics, 2015)
Background: Health Information Management (HIM) and Health Informatics (HI) were very separate professions when they were first formed. However, with the increasing adoption of electronic health records, the interests of the two fields have become more aligned.Objectives: To describe the evolution of a joint master’s program in health informatics(HI) and health information management (HIM)Methods: After analyzing workforce needs, and reviewing both CAHIIM accreditation requirements and existing curricular offerings in separate programs in HIM and HI, a joint program was developed.Results: An HI master’s program with a core curriculum for all students and tracks in Data Analytics, User Experience and Advanced Practice HIM was developed. A model for a comprehensive examination, based on the CAHIIM competencies, to be administered prior to and after the core curriculum was also developed.Conclusions: A core and track curriculum that incorporates HIM education as part of the Master of Science of Health Informatics provides a feasible roadmap for the future as HIM and HI become more closely aligned.Citation: Dorsey AD, Clements K, Garrie RL, Houser SH, Berner ES. Bridging the gap – a collaborative ppproach to health information management and informatics education. Appl Clin Inf 2015; 6: 211–223http://dx.doi.org/10.4338/ACI-2014-09-RA-0083
Keywords: Health informatics education; health information management education; comprehensive exam